Self-cleaning ink and preparation method thereof
By using bicans anatase TiO2 in UV ink, dynamic protection is achieved by using the synergistic effect of the inner shell SiO2 and the outer shell light-responsive polyurethane, the problem of damage to the printing layer by anatase titanium dioxide during the photocatalytic self-cleaning process is solved, and good self-cleaning ability and coating life are maintained.
Patent Information
- Application Number
- CN202510280470.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-05-16
- Estimated Expiration
- 2045-03-11
AI Technical Summary
The free radicals generated by the anatase titanium dioxide used in existing UV inks during photocatalytic self-cleaning will oxidize and decompose the printing layer, resulting in discoloration and aging, and the single-layer coating structure cannot effectively balance the photocatalytic activity and protection functions.
Bihull anatase TiO2 is used to achieve dynamic protection through the synergy between the inner shell SiO2 and the outer shell light-responsive polyurethane. The inner shell SiO2 forms a dense inorganic layer through atomic layer deposition technology to prevent the migration of photogenerated holes into the ink; the outer shell layer can decompose visible light at a specific wavelength, activates the photocatalytic activity of TiO2 and achieves self-cleaning on demand.
While maintaining good self-cleaning ability, it reduces the destructive effect of free radicals on the printing layer, extends the life of the coating, and improves the application prospects of inks.
Smart Images

Figure BDA0005305511420000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ink, and in particular to a self-cleaning ink and a preparation method thereof. Background Art
[0002] Currently, UV light-curing inks are widely used in the printing industry. UV inks can be cured in seconds by ultraviolet irradiation, without the oxidation drying process of traditional inks, which improves the efficiency of printing and is especially suitable for high-speed automated production lines. At the same time, UV inks do not contain volatile organic compounds, which is in line with the trend of green industrial development. Moreover, the cured ink film has the advantages of wear resistance, water resistance, solvent resistance, and a more saturated appearance.
[0003] However, although traditional UV inks claim to be solvent-free, they still contain some volatile components. By adding catalysts for self-cleaning, residual solvents can be further reduced or eliminated, improving safety performance. Although the anatase titanium dioxide used in existing UV inks has photocatalytic self-cleaning functions, the free radicals it produces will oxidize and decompose the printed layer, causing discoloration and aging. Current technology mainly inhibits free radical leakage through single-layer coating, but there are the following problems: 1. Conventional static protection uses a single-layer coating structure, and the coating layer may completely shield the photocatalytic activity, making the self-cleaning function ineffective; 2. Due to the single nature of the coating structure, when anatase titanium dioxide generates free radicals, the diffusion process of the free radicals is relatively random, which can easily cause damage to the inside of the printed layer.
[0004] In view of this, how to reduce the destructive effect of titanium dioxide on the printed layer while maintaining good decontamination and self-cleaning capabilities has become one of the technical problems that need to be solved urgently. Summary of the invention
[0005] In view of this, in order to solve the above-mentioned deficiencies in the prior art, the present invention provides a self-cleaning ink and a preparation method thereof which can reduce the damage to the printing layer.
[0006] The technical solution of the present invention is implemented as follows: The present invention provides a self-cleaning ink, the raw materials of which are calculated by weight and include: 40-50 parts of prepolymer, 20-30 parts of diluent, 5-8 parts of photoinitiator, 8-12 parts of double-shell rutile TiO2, 3-5 parts of dispersant, and 2-4 parts of auxiliary agent. The double-shell rutile TiO2 includes an inner shell layer and an outer shell layer, the inner shell layer is SiO2, and the outer shell layer is photoresponsive polyurethane.
[0007] In some embodiments, the method for preparing double-shell anatase TiO2 comprises the following steps:
[0008] S1. Dissolve tetrabutyl titanate in an ethanol aqueous solution, ethanol: water = 1:3 (v:v), adjust the pH value to 3, heat to 80°C for 12 hours, centrifuge, wash, and dry at 60°C for 12 hours to obtain anatase TiO2 nanoparticles;
[0009] S2, placing the TiO2 nanoparticles prepared in step 1 in the reaction chamber of an atomic deposition device, using SiCl4 as a silicon source and water as an oxidant, and performing 50 cycles at a deposition temperature of 200°C, introducing SiCl4 for 0.5s and water for 1s in each cycle, to prepare TiO2 nanoparticles with SiO2 deposited on the surface;
[0010] S3, disperse the SiO2@TiO2 prepared in step 2 in the ethyl acetate solution of polyurethane prepolymer containing azobenzene groups, 365nm, 10mW / cm 2 UV curing is performed for 10-60 seconds to form a cross-linked outer shell layer, and double-shell anatase TiO2 is obtained after filtering and washing.
[0011] In the above scheme, double-shelled anatase TiO2 is used to achieve dynamic protection through the synergistic effect of the inner SiO2 layer and the outer photoresponsive polyurethane layer. The inner SiO2 layer uses atomic layer deposition technology to form a dense inorganic layer, which blocks the migration of photogenerated holes into the ink through physical isolation, reducing the oxidative damage of free radicals to the organic matrix; the polyurethane containing azobenzene groups is stable after UV curing, but can be degraded under a specific wavelength of visible light (450-550nm), exposing the inner shell layer and activating the photocatalytic activity of TiO2, achieving on-demand self-cleaning. When not activated, the outer shell shields ultraviolet rays and inhibits the photocatalytic reaction; when activated, the outer shell degrades and releases the activity of TiO2, balancing the self-cleaning needs and matrix protection.
[0012] In some embodiments, in S1, before the heating and insulation reaction, it also includes: adding Fe(NO3)3 and NH4F to the ethanol aqueous solution, the amount of Fe(NO3)3 is 1-3% of the molar amount of TiO2, and the amount of NH4F is 5-8% of the molar amount of TiO2.
[0013] In the above embodiment, Fe 3+ and F - Co-doping optimizes the radical migration direction through the following mechanisms: Fe 3+ Replacement Ti 4 + Introducing an intermediate energy level, reducing the band gap to 2.8eV, and enhancing the visible light response; F -Adsorbing surface hydroxyl groups optimizes the conduction band to -0.6eV, driving holes to migrate preferentially to the surface. The hole migration path is shortened, reducing penetration into the ink, improving self-cleaning efficiency, forming a carrier "high-speed channel", suppressing the electron-hole recombination rate, and reducing the risk of internal damage.
[0014] In some embodiments, in S3, the mass ratio of SiO2@TiO2 to the polyurethane prepolymer containing azobenzene groups is 1:(1-1.5).
[0015] The polyurethane prepolymer containing azobenzene groups can be directly purchased or prepared. The preparation method includes:
[0016] a) reacting polytetrahydrofuran (Mn=2,000) with isophorone diisocyanate at 70° C. for 4 h to obtain a prepolymer having an NCO content of 6-8%;
[0017] b) adding 4,4'-dihydroxyazobenzene (10 mol%) and continuing the reaction for 2 h;
[0018] c) removing unreacted monomers by distillation under reduced pressure to obtain a prepolymer having a molecular weight of 12,000±500 g / mol and an azobenzene content of 10 mol%.
[0019] In some embodiments, the photoinitiator includes a thiol, and the thiol includes at least one of 1-decanethiol and 1-nonanethiol.
[0020] In some embodiments, the photoinitiator further comprises camphorquinone, and the mass ratio of thiol to camphorquinone is 3:2.
[0021] In the above embodiment, the prepolymer is cross-linked quickly initiated by sulfhydryl free radicals, the curing time is shortened to 0.5s, the possibility of oxidation of uncured residues is reduced, and camphorquinone extends the absorption wavelength to 450nm, which matches the visible light response of Fe / F-TiO2, and synergistically improves the curing efficiency; after curing, a dense cross-linked network is formed, the porosity of the ink is reduced, and the free radicals are blocked from penetrating into the interior of the printed layer.
[0022] In some embodiments, the auxiliary agent includes a leveling agent, and the leveling agent is a polysiloxane leveling agent BYK-307.
[0023] In some embodiments, the auxiliary agent further comprises carboxylated carbon quantum dots, the particle size of which is 2-5 nm, and the mass ratio of the quantum dots to the leveling agent is 1:2.
[0024] In the above implementation, the polysiloxane structure reduces the surface tension of the ink, ensures the uniformity of the coating, and avoids damage caused by excessive local TiO2 concentration. The carboxylated carbon quantum dots adsorb escaped free radicals through π-π action and catalyze their conversion into CO2 / H2O. The mass ratio of the quantum dots to the leveling agent is 1:2, which balances the free radical capture and the leveling performance of the ink and reduces the cumulative damage to the substrate.
[0025] In some embodiments, the prepolymer includes at least one of polyurethane acrylate and epoxy acrylate, the diluent includes at least one of DCPD and HDDA, and the dispersant includes at least one of hyperbranched acrylate oligomer and polyether-modified polysiloxane.
[0026] In a second aspect, the present invention further provides a method for preparing the above-mentioned ink, comprising the following steps:
[0027] Step 1: Stir the prepolymer, diluent and photoinitiator at 45-55°C for 30-60 minutes until homogeneous;
[0028] Step 2: Add double-shell TiO2 and dispersant, and ball mill at 200-400rpm for 20-40min
[0029] Step 3: After vacuum degassing at -0.1 MPa for 30 minutes, add the additive and mix well to obtain a self-cleaning ink.
[0030] In some embodiments, in step 2, the ball milling temperature is 25-30° C., and the ball milling uses zirconium oxide beads with a diameter of 0.3 mm.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] Compared with the traditional TiO2 self-cleaning solution, this application adopts double-shell titanium dioxide, which solves the contradiction between photocatalytic activity and collective protection through the synergistic solution of dynamic coating, energy band regulation and free radical capture. While maintaining good self-cleaning ability, it also maintains the life of the coating and has good application prospects. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.
[0035] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.
[0036] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.
[0037] Example 1
[0038] This embodiment provides a technical solution of combining double-shell TiO2 with a conventional photoinitiator.
[0039] The ingredients are as follows:
[0040] Prepolymer polyurethane acrylate 45 parts, diluent HDDA 25 parts, photoinitiator TPO 6 parts, double-shell TiO2 10 parts, dispersant hyperbranched acrylate 4 parts, leveling agent BYK-307 3 parts.
[0041] The preparation method of double-shell TiO2 is as follows:
[0042] 0.2 mol of tetrabutyl titanate was dissolved in 1 L of ethanol aqueous solution, ethanol: water = 1:3 (v:v), the pH value was adjusted to 3, heated to 80°C for 12 h, centrifuged, washed and dried at 60°C for 12 h to obtain anatase TiO2 nanoparticles;
[0043] The prepared TiO2 nanoparticles were placed in a reaction chamber of an atomic deposition device, SiCl4 was used as a silicon source, water was used as an oxidant, and the deposition temperature was 200°C. 50 cycles were performed, and SiCl4 was introduced for 0.5s and water for 1s in each cycle, thereby preparing TiO2 nanoparticles with SiO2 deposited on the surface.
[0044] The prepared SiO2@TiO2 was dispersed in an ethyl acetate solution of a polyurethane prepolymer containing azobenzene groups, wherein the mass ratio of SiO2@TiO2 to the polyurethane prepolymer containing azobenzene groups was 1:1. UV curing was carried out at 365nm, 10mW / cm2 ultraviolet light for 30s to form a cross-linked outer shell layer, and double-shell rutile TiO2 was obtained after filtration and washing.
[0045] The preparation method of the above-mentioned polyurethane prepolymer containing azobenzene group is as follows:
[0046] a) reacting polytetrahydrofuran (Mn=2,000) with isophorone diisocyanate at 70° C. for 4 h to obtain a prepolymer having an NCO content of 6-8%;
[0047] b) adding 4,4'-dihydroxyazobenzene (10 mol%) and continuing the reaction for 2 h;
[0048] c) removing unreacted monomers by distillation under reduced pressure to obtain a prepolymer having a molecular weight of 12,000±500 g / mol and an azobenzene content of 10 mol%.
[0049] Preparation method of self-cleaning ink:
[0050] Step 1: Stir the prepolymer, diluent and photoinitiator at 50°C for 30 minutes until homogeneous;
[0051] Step 2: Add double-shell TiO2 and dispersant, and ball mill at 300rpm for 30min
[0052] Step 3: After vacuum degassing at -0.1 MPa for 30 minutes, add the additive and mix well to obtain a self-cleaning ink.
[0053] Example 2
[0054] This embodiment uses Fe / F doped double-shell TiO2 on the basis of embodiment 1, and uses a thiol-camphorquinone composite photoinitiator, and other conditions remain unchanged, specifically:
[0055] The ingredients are as follows:
[0056] 45 parts of prepolymer polyurethane acrylate, 25 parts of diluent HDDA, 6 parts of photoinitiator, composed of 1-decyl mercaptan: camphorquinone mass ratio = 3:2, 10 parts of Fe / F doped double shell TiO2, 4 parts of dispersant hyperbranched acrylate, and 3 parts of leveling agent BYK-307.
[0057] The preparation method of Fe / F doped double shell TiO2 is as follows:
[0058] 0.2 mol of tetrabutyl titanate was dissolved in 1 L of ethanol aqueous solution, ethanol: water = 1:3 (v:v), the pH value was adjusted to 3, and then 0.002 mol of Fe(NO3)3 and 0.01 mol of NH4F were added and heated to 80°C for 12 h, and then centrifuged, washed and dried at 60°C for 12 h to obtain anatase TiO2 nanoparticles;
[0059] The prepared TiO2 nanoparticles were placed in a reaction chamber of an atomic deposition device, SiCl4 was used as a silicon source, water was used as an oxidant, and the deposition temperature was 200°C. 50 cycles were performed, and SiCl4 was introduced for 0.5s and water for 1s in each cycle, thereby preparing TiO2 nanoparticles with SiO2 deposited on the surface.
[0060] The prepared SiO2@TiO2 was dispersed in an ethyl acetate solution of a polyurethane prepolymer containing azobenzene groups, wherein the mass ratio of SiO2@TiO2 to the polyurethane prepolymer containing azobenzene groups was 1:1. UV curing was carried out at 365nm, 10mW / cm2 ultraviolet light for 30s to form a cross-linked outer shell layer, and double-shell rutile TiO2 was obtained after filtration and washing.
[0061] Example 3
[0062] This embodiment, based on the embodiment 2, adopts a higher ratio of Fe / F doped double-shell TiO2, and uses a thiol-camphorquinone composite photoinitiator, and other conditions remain unchanged, specifically:
[0063] In the preparation method of Fe / F doped double shell TiO2:
[0064] 0.2 mol of tetrabutyl titanate was dissolved in 1 L of ethanol aqueous solution, ethanol: water = 1:3 (v:v), and the pH value was adjusted to 3. Then 0.006 mol of Fe(NO3)3 and 0.016 mol of NH4F were added, heated to 80°C and kept for reaction for 12 hours. After centrifugation and washing, it was dried at 60°C for 12 hours to obtain rutile TiO2 nanoparticles. The subsequent steps were the same as those in Example 2.
[0065] Example 4
[0066] On the basis of Example 2, this example further introduces carboxylated carbon quantum dots, whose particle size is 2-5 nm and whose mass ratio to the leveling agent BYK-307 is 1:2.
[0067] Comparative Example 1
[0068] This comparative example is based on Example 1, and adopts a polyurethane shell without light response, and other conditions remain unchanged, with the following differences:
[0069] The prepared SiO2@TiO2 was dispersed in an ethyl acetate solution of a polyurethane prepolymer, wherein the mass ratio of SiO2@TiO2 to the polyurethane prepolymer was 1:1, and UV-cured for 30 seconds at 365 nm and 10 mW / cm2 of ultraviolet light to form a cross-linked outer shell layer. After filtration and washing, a double-shell rutile TiO2 was obtained.
[0070] The preparation method of the polyurethane prepolymer is as follows:
[0071] a) reacting polytetrahydrofuran (Mn=2,000) with isophorone diisocyanate at 70° C. for 4 h to obtain a prepolymer having an NCO content of 6-8%;
[0072] b) removing unreacted monomers by distillation under reduced pressure to obtain a polyurethane prepolymer.
[0073] Comparative Example 2
[0074] This comparative example is based on Example 2, in which the double-shell TiO2 is not doped with Fe / F, and the other steps are the same, with the following specific differences:
[0075] 0.2 mol of tetrabutyl titanate was dissolved in 1 L of ethanol aqueous solution, ethanol: water = 1:3 (v:v), the pH value was adjusted to 3, heated to 80°C for 12 hours, centrifuged, washed and dried at 60°C for 12 hours to obtain anatase TiO2 nanoparticles; other parameters and steps were the same as in Example 2.
[0076] Comparative Example 3
[0077] This comparative example is based on Example 2, and uses TPO photoinitiator to replace the thiol-camphorquinone composite system.
[0078] The performance of the inks prepared in the above different embodiments and comparative examples was verified.
[0079] The ink was applied to the glass surface, cured by UV, and then the above tests were performed.
[0080] Self-cleaning efficiency
[0081] According to ISO 10678:2010 (Degradation performance of organic matter in aqueous solution of photocatalytic materials), a methylene blue solution (0.1 g / L) was sprayed to form a pollution layer, and then placed under a 450 nm LED light source (light intensity 50 mW / cm 2 ) for 24 h, and the absorbance change of methylene blue at 664 nm was measured using a UV-visible spectrophotometer to calculate the degradation rate.
[0082] The self-cleaning efficiency comparison is as follows:
[0083] Grouping Methylene blue degradation rate Example 1 85% Example 2 95% Example 3 98% Example 4 96% Comparative Example 1 45% Comparative Example 2 60% Comparative Example 3 75%
[0084] Ink durability test
[0085] Use QUV accelerated aging test chamber (UVA-340 lamp, irradiation intensity 0.76W / m 2 , 60℃ light / 50℃ condensation cycle), after 1000 hours of testing:
[0086] Color difference (ΔE): Use a colorimeter (such as X-Rite Ci64) to measure the Lab* values before and after aging and calculate ΔE (ΔE<2 is excellent, ΔE>5 is significantly deteriorated).
[0087] Free radical penetration depth and residual amount
[0088] ESR test:
[0089] The concentration of OH radicals in the ink (unit: μmol / g) was detected using an electron paramagnetic resonance spectrometer (ESR) to compare the penetration depths of different embodiments / comparative examples.
[0090] Fluorescent probe method:
[0091] Terephthalic acid (TA) was used as a fluorescent probe to react with ·OH to generate 2-hydroxyterephthalic acid (the fluorescence intensity was positively correlated with the ·OH concentration), and the residual free radicals were quantitatively determined by a fluorescence spectrophotometer (excitation wavelength 315 nm, emission wavelength 425 nm).
[0092] Band structure and photoresponse characteristics
[0093] UV-Vis DRS Test:
[0094] The band gap value (Eg) of TiO2 was determined by UV-visible diffuse reflectance spectroscopy (DRS), and the data was converted by the Kubelka-Munk equation to verify the regulating effect of Fe / F doping on the energy band.
[0095] Photoresponse degradation threshold:
[0096] The coating was irradiated with light sources of different wavelengths (365nm, 450nm, 550nm) to measure the degradation time (seconds) of the outer shell layer and the triggering threshold of the photocatalytic activity.
[0097] Curing time and mechanical properties
[0098] Determination of curing time:
[0099] Use UV curing machine (365nm, 10mW / cm 2 ) irradiate the ink coating, monitor the double bond conversion rate in real time by FTIR (>95% is complete curing), and record the required time.
[0100] Mechanical properties test:
[0101] Hardness: Tested according to ASTM D3363 pencil hardness method (H-9H).
[0102] Abrasion resistance: tested according to ASTM D4060 Taber abrasion tester (500 g load, mass loss mg after 1000 cycles).
[0103] The test results of substrate protection effect are as follows:
[0104]
[0105] Band structure and photoresponse threshold
[0106] Grouping Bandgap(eV) Photoresponse threshold(nm) Example 2 2.8 450 Example 3 2.5 550 Comparative Example 2 3.2 388
[0107] Comparison of the data of Example 1 with Comparative Example 1 shows that the dynamic light-responsive shell increases the self-cleaning efficiency from 45% to 85%, and reduces ΔE from 5.8 to 2.5. Comparison of the data of Example 2 with Comparative Example 2 shows that Fe / F doping reduces the band gap from 3.2 eV to 2.8 eV, and increases the self-cleaning efficiency from 60% to 95%. Comparison of the data of Example 2 with Comparative Example 3 shows that the thiol-camphorquinone system shortens the curing time from 2 seconds to 0.5 seconds, and reduces the residual free radicals by 67%.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A self-cleaning ink, characterized in that: Calculated by weight, it includes: 40-50 parts of prepolymer, 20-30 parts of diluent, 5-8 parts of photoinitiator, 8-12 parts of double-shell rutile TiO2, 3-5 parts of dispersant, and 2-4 parts of auxiliary agent. The double-shell rutile TiO2 includes an inner shell layer and an outer shell layer, the inner shell layer is SiO2, and the outer shell layer is photoresponsive polyurethane.
2. The self-cleaning ink according to claim 1, characterized in that: The preparation method of double-shell anatase TiO2 comprises the following steps: S1. Dissolve tetrabutyl titanate in an ethanol aqueous solution, ethanol: water = 1:3 (v:v), adjust the pH value to 3, heat to 80°C for 12 hours, centrifuge, wash, and dry at 60°C for 12 hours to obtain anatase TiO2 nanoparticles; S2, placing the prepared TiO2 nanoparticles in a reaction chamber of an atomic deposition device, using SiCl4 as a silicon source and water as an oxidant, at a deposition temperature of 200°C, performing 50 cycles, introducing SiCl4 for 0.5s and water for 1s in each cycle, to prepare TiO2 nanoparticles with SiO2 deposited on the surface; S3, disperse the prepared SiO2@TiO2 in the ethyl acetate solution of polyurethane prepolymer containing azobenzene groups, 365nm, 10mW / cm 2 UV curing is performed for 10-60 seconds to form a cross-linked outer shell layer, and double-shell anatase TiO2 is obtained after filtering and washing.
3. The self-cleaning ink according to claim 2, characterized in that: In S1, before the heating and insulation reaction, it also includes: adding Fe(NO3)3 and NH4F to the ethanol aqueous solution, the amount of Fe(NO3)3 is 1-3% of the molar amount of TiO2, and the amount of NH4F is 5-8% of the molar amount of TiO2.
4. The self-cleaning ink according to claim 1, characterized in that: The photoinitiator includes thiol, and the thiol includes at least one of 1-decanethiol and 1-nonanethiol.
5. The self-cleaning ink according to claim 4, characterized in that: The photoinitiator further comprises camphorquinone, and the mass ratio of thiol to camphorquinone is 3:
2.
6. The self-cleaning ink according to claim 1, characterized in that: The auxiliary agent includes a leveling agent, and the leveling agent is a polysiloxane leveling agent BYK-307.
7. The self-cleaning ink according to claim 6, characterized in that: The auxiliary agent also includes carboxylated carbon quantum dots with a particle size of 2-5 nm, and the mass ratio of the quantum dots to the leveling agent is 1:
2.
8. The self-cleaning ink according to claim 1, characterized in that: The prepolymer includes at least one of polyurethane acrylate and epoxy acrylate, the diluent includes at least one of DCPD and HDDA, and the dispersant includes at least one of hyperbranched acrylate oligomer and polyether-modified polysiloxane.
9. The method for preparing the self-cleaning ink according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: Stir the prepolymer, diluent and photoinitiator at 45-55°C for 30-60 minutes until homogeneous; Step 2: Add double-shell TiO2 and dispersant, and ball mill at 200-400rpm for 20-40min Step 3: After vacuum degassing at -0.1 MPa for 30 minutes, add the additive and mix well to obtain a self-cleaning ink.
10. The method for preparing the self-cleaning ink according to claim 9, characterized in that: In step 2, the ball milling temperature is 25-30°C.
Citation Information
Patent Citations
Ophthalmic Lenses Comprising a Photodegradation Protection Coating and a Process for Producing Such Lenses
US20070179224A1
Coating composition and coated article
US20190225821A1
Photoresponsive materials for volumetric additive manufacturing
US20210379819A1
Cited By
High-stripping-force oil-proofing agent emulsion as well as preparation method and application thereof
CN120484551A